Suicidal Behaviors Among Active-Duty US Service Members: Data from the 2018 Health-Related Behaviors Survey - Ahmed AE; Yim MH; Dawood J; Olsen CH; Waters AJ; Singer DE; Mancuso JD (Psychology Research and Behavior Management, 2023)
Anwar E Ahmed,1 Michael H Yim,1 Jimmy Dawood,2 Cara H Olsen,1 Andrew J Waters,3 Darrell E Singer,1 James D Mancuso1 1Department of Preventive Medicine & Biostatistics, Uniformed Services University of the Health Sciences, Bethesda, MD, 20814, USA; 2School of Medicine, Uniformed Services University of the Health Sciences, Bethesda, MD, 20814, USA; 3Department of Medical and Clinical Psychology, Uniformed Services University of the Health Sciences, Bethesda, MD, 20814, USACorrespondence: Anwar E Ahmed, Department of Preventive Medicine & Biostatistics, Uniformed Services University of the Health Sciences, Bethesda, MD, 20814, USA, Email anwar.ahmed@usuhs.eduBackground: This study aimed to 1) determine the prevalence of past-year suicidal ideation (SI) and attempts (SA) among active-duty SMs; 2) determine whether differences exist by age, sex, and race; and 3) assess whether prevalence estimates vary by risk profiles of mental health conditions and substance use.Methods: Data were from the 2018 Health-Related Behavior Survey (HRBS), a cross-sectional survey of active-duty SMs (n = 17,166). We used the logistic model to identify the factors of SI and SA and latent class analysis (LCA) to identify the risk profiles.Results: Among active duty SMs, 8.26% had SI and 1.25% had SA in the past year. Gender and age have been shown to influence how race might contribute to suicidal behaviors. Mental health conditions were associated with higher odds of SI and SA, as were younger ages; LGB identity; being separated, divorced, or widowed; use of e-cigarettes, dual use of e-cigarettes and cigarettes, or drugs; and history of deployment of less than 12 months. Frequencies of cigarette and e-cigarette use were also associated with SI and SA, indicating the odds were increasing by 0.3% for every additional cigarette or e-cigarette used. Five risk profiles were identified: class 1 (illegal drug use), class 2 (mental health needs with tobacco and alcohol use), class 3 (mental health conditions only), class 4 (“low risk” SMs with low levels of illegal drug use, mental health visits, tobacco use, and alcohol use), and class 5 (alcohol use). Compared to class 4 (“low risk”), all other risk profiles were associated with increased odds of suicidal behaviors.Conclusion: Despite the resources and increased access provided for mental health support, the prevalence of SI among active-duty SMs is greater than in the general population of the same age, likely due to additional military exposures and stressors.Keywords: suicide, ideation, attempts, mental health, e-cigarette, active-duty service member